“Mightier than death, untamable by fate”: Felicia Hemans’s Byronic Heroines and the Sorority of the Domestic Affections - Osman, Sharifah (Romanticism on the Net)

(untitled) (Université de Montréal, 2006)
AbstractThis article argues that Byron’s rehabilitation of the abject figure of the Oriental woman in his verse romances serves as a popular model of female heroism for Felicia Hemans. The orientalized Byronic heroines that appear in Hemans’s poems challenge stereotypical representations of femininity through their unorthodox acts of self-assertion—often engaging in violence and even suicide as a means of avenging the loss of familial ties or emancipating themselves from their oppressive circumstances. Defiant heroines like Eudora in “The Bride of the Greek Isle,” Maimuna in “The Indian City” and a whole host of other distraught yet resolute women who insist on reclaiming their dignity and humanity through acts of violence and self-destruction, all reflect the poet’s persistent, even obsessive, meditations on the role of the Eastern woman in the formation of English national consciousness. As the feminized embodiment of Britain’s “self-consolidating Other”, Hemans’s Byronic heroines serve not only as potent symbols of English ambivalence towards racial and cultural difference but also reveal the various inconsistencies of nineteenth-century British society by drawing attention to issues of nationalism and gender closer to home. Placed in the most trying emotional states, these heroines retaliate with impressive displays of agency and courage, and their actions allow Hemans not only to call into question the innate masculinity of acts of valor and sacrifice, but also to underscore the sorority of female suffering. More significantly, the poet’s sympathetic portrayal of her Byronic heroines in the poems discussed --a depiction that links these heroines’ psychological rebellion with the domestic affections-- enables her to promote the feminized idea of the British nation, and by implication, the British Empire, as a political commonwealth based on an ethic of care and tolerance.